DEVELOPMENT OF A DIGITAL SELF-PORTRAIT DRAWING LEARNING RESOURCE BASED ON IBIS PAINT X FOR VISUAL JOURNALING IN JUNIOR HIGH SCHOOL - Hareza Lutfi Fauzi; Indar Sabri; Arif Hidajad; Welly Suryandoko (Journal of Practice Learning and Educational Development, 2026)
This research aims to develop a digital character drawing learning medium based on the Ibis Paint X application for visual journal learning in junior high school students. The study employed a Research and Development (R&D) method using the Dick and Carey instructional design model, which consists of ten systematic stages. The resulting product is a digital learning medium comprising modules, video tutorials, and examples of visual artworks. Validation by content and media experts indicated that the developed medium is suitable for use. Trial results from individual, small group, and field tests demonstrated improvements in student creativity, learning motivation, and active engagement in visual arts learning. These findings suggest that contextually relevant digital learning media effectively support visual arts learning outcomes within the Merdeka Curriculum framework.